A preliminary investigation into the growth of the Sisters scoria cone complex, Ascension Island. - WINSTANLEY, REBECCA (2020)
Ascension Island, located in the South Atlantic Ocean, is an active ocean island volcano and a British Overseas Territory with strategically important UK and USA military infrastructure. The most recent eruption occurred from the Sisters scoria cone complex (SSCC) in the north of the island, which is composed of at least 4 scoria cones, tephra fall deposits and lavas. Here I present a textural study of the Unit 3 tephra fall deposit from two locations, as well as tephra dispersal analysis. Petrographic analysis of a further three tephra fall deposits and nine lava samples from the Sisters scoria cone complex was also undertaken in an attempt to correlate the lava flows and tephra falls. Three distinct types of pyroclasts were identified: type 1, which are equant and platy shaped with a dull, wrinkly skin that is adhered with ash fragments, lithic clasts, Pele’s hair, spherical lava droplets and mineral precipitates. Their interiors are moderately-highly vesicular with a moderate microlite content; type 2, which are elongate and fluidal shaped with a black, glassy skin. Their interiors range from poorly-highly vesicular with a moderate microlite content; type 3, which range from elongate and fluidal to equant and sub-angular with a golden brown, glassy skin. Their interiors are highly vesicular with a poor microlite content. The Unit 3 eruption began with locally dispersed Hawaiian lava fountaining, before transitioning to Strombolian explosions that were more widely dispersed. As the eruption continued Strombolian explosions became dominant. Towards the end of the eruption, the magma came into contact with a limited volume of groundwater, which led to a series of small-scale, weak phreatomagmatic explosions, separated by magmatic phases. The Unit 3 eruption covered >24 km2 of the island and a similar eruption in the future would have a 50% chance of ash accumulation up to 2.5 cm (10 kg/m2) thick over Georgetown. The other eruptions that contributed to the Sisters scoria cone complex are inferred to have been ...